Exploring the LEACH routing protocol in wireless sensor networks: a brief analysis - Rita de Fátima Muniz (Big Data and Computing Visions)
Wireless Sensor Network (WSN) are in great demand from the recent years, as nowadays we have seen a wide growth of wireless devices including cellular phones, laptops, mobiles, PDA’s etc. WSNs consists of thousands of tiny sensor nodes. In a WSN a node is no longer useful when its battery dies, so to avoid this problem many protocols were introduced, but most of the rank is given to hierarchical routing protocols. In this paper, we analyze LEACH protocol, its phases, advantages and disadvantages and various kinds of attacks on this routing protocol.